Developing a typology for mission-oriented innovation policies - Florian Wittmann; Miriam Hufnagl; Ralf Lindner; Florian Roth; Jakob Edler (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2020)
The goal to address broader societal problems by mission-oriented research and inno-vation policy has brought new demands for the governance and implementation to the forefront and led to a great diversity of missions. By developing a typology for the clas-sification of different types of missions, this working paper can serve as a first step for studying the impact of the missions of the German High-Tech Strategy 2025 (HTS). Combining existing literature on mission-oriented innovation policy with insights from governance structures, we identify four types of missions - two subtypes of transformer and accelerator missions each - and demonstrate that this typology can be successfully applied to the 12 missions of the German HTS 2025. Thereby, we contribute to a more fine-grained understanding of the different demands and challenges inherent to different missions and thus provide the opportunity for a systematic comparison and a reflection on the varying requirements for assessing the impact of mission-oriented policies.
urn:nbn:de:0011-n-5862912
Keywords: 330; Technologiepolitik; Innovation; Klassifikation; Hochtechnologie; Deutschland